Dissipative measure-valued solutions to the magnetohydrodynamic equations - Yang, Jianwei; Wang, Huimin; Shi, Qihong (Mathematical Modelling and Analysis, 2025)
In this paper, we study the dissipative measure-valued solution to the magnetohydrodynamic equations of 3D compressible isentropic flows with the adiabatic exponent γ > 1 and prove that a dissipative measure-valued solution is the same as the standard smooth classical solution as long as the latter exists, provided they emanate from the same initial data (weak–strong) uniqueness principle.